2021
DOI: 10.48550/arxiv.2105.02530
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Interfacial strain relief by periodic dislocation doublets emerging from rotationally related orientation relationships of Y4Zr3O12 dispersions in ferrite matrix

Abstract: The trigonal/bcc orientation relationships (ORs) and their likelihood of occurrence are extensively studied using dispersed Y 4 Zr 3 O 12 (δ) nano-precipitates in bcc Fe (α) matrix by means of transmission electron microscopy, image simulations and a crystallographic model. Two orientation relationships related by a rotation:[1 20] δ ||[111] α with (21 2) δ ||( 110) α and [1 20] δ ||[111] α with (00 3) δ ||( 110) α , are established and periodic arrays of misfit dislocation doublets are identified at the strai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 43 publications
(31 reference statements)
1
0
0
Order By: Relevance
“…Nearly 74% of the precipitates in the replica possess phase contrast of Figure 3(a) and power spectrum similar to Figure 3(b), which can be indexed for < 1 20 > or < 2 10 > directions of Y 4 Zr 3 O 12 shown in Figure 3(d). Earlier multislice simulations indicated that the < 1 20 > δ produces 'spot-like' contrast in HRTEM images and < 2 10 > δ is characterized by a 'line like' contrast [18]. The contrast observed in the current study is exactly similar to the contrast of < 1 20 > δ ,as superimposed in the Bragg filtered image Figure 3(d).…”
supporting
confidence: 81%
“…Nearly 74% of the precipitates in the replica possess phase contrast of Figure 3(a) and power spectrum similar to Figure 3(b), which can be indexed for < 1 20 > or < 2 10 > directions of Y 4 Zr 3 O 12 shown in Figure 3(d). Earlier multislice simulations indicated that the < 1 20 > δ produces 'spot-like' contrast in HRTEM images and < 2 10 > δ is characterized by a 'line like' contrast [18]. The contrast observed in the current study is exactly similar to the contrast of < 1 20 > δ ,as superimposed in the Bragg filtered image Figure 3(d).…”
supporting
confidence: 81%